How Do Empowered Leaders Influence the Job Satisfaction of Kindergarten Teachers in China? Evidence From Mediation Analysis - Liu, Li; Yang, Chuan; Huang, Dawei (Frontiers in Psychology, 2021)
Given the current shortage of kindergarten teachers, this study examines the relationship between empowering leadership and job satisfaction among kindergarten teachers in China from the perspective of their job characteristics and the Chinese cultural context. The participants were 557 Chinese kindergarten female teachers whose average number of years of experience was 2.82 (SD = 3.02). They completed a self-report survey regarding empowering leadership, vigor, affective commitment, and job satisfaction. The study results show that vigor and affective commitment could mediate the relationship between empowering leadership and job satisfaction. Finally, we discuss the findings of this study in depth. At the same time, we suggest that administrators should focus on the empowering leadership of Chinese kindergarten teachers, strive to increase their level of dynamism, and finally, strengthen the emotional connection between the organization and the Chinese kindergarten teachers.Thus, we suggest that educational administrators should empower kindergarten teachers more, rather than allowing them to be mere enforcers. In addition, how to enhance the individual dynamics of early childhood teachers and their emotional connection to the organization may also be something for educational administrators to consider.